Project teams: selected topics - Winkler, Renata (Management Sciences, 2017)
The purpose of this study is to present and analyze those topics that are crucial from the point of view of the functioning of project teams. The article presents issues referring to the improvement and development of a project team. It includes following deliberations on the selection of team members, building the team, training and leadership. The article was drawn up on the basis of the review of the literature on the subject
Nauki o Zarządzaniu = Management Sciences, 2017, Nr 1 (30), s. 31-37
Keywords: project team; leadership; training; zespół projektowy; przywództwo; szkolenie